The Chlamydia muridarum Organisms Fail to Auto-Inoculate the Mouse Genital Tract after Colonization in the Gastrointestinal Tract for 70 days. - Luying Wang; Qi Zhang; Tianyuan Zhang; Yuyang Zhang; Cuiming Zhu; Xin Sun; Nu Zhang; Min Xue; Guangming Zhong (PLoS ONE, 2016)
Chlamydia muridarum is known to colonize in the gastrointestinal tract for long periods of time, which has been hypothesized to serve as a reservoir for spreading to the genital tract. To test this hypothesis, a luciferase-expressing C. muridarum was used to establish a long-lasting infection in the mouse gastrointestinal tract following either intragastric or intrarectal inoculations. In vivo imaging revealed significant bioluminescent signals mainly in the mouse abdominal area throughout the experiments. Ex vivo imaging localized the signals to the mouse gastrointestinal tract, which was confirmed by monitoring the C. muridarum organisms in the mouse organs/tissues. Despite the long-lasting colonization in the gastrointestinal tract and active shedding of infectious organisms in the rectal swabs, the organisms did not cause any significant infection or pathology in the genital tract throughout the experiments, which was reproduced in multiple strains of mice and with an increased inoculation dose to the gastrointestinal tract. The above observations have demonstrated that the long-lasting C. muridarum organisms from the gastrointestinal tract are inefficient in auto-inoculating the genital tract, suggesting that the gastrointestinal tract Chlamydia may utilize an indirect mechanism to affect its pathogenicity in the genital tract.